Optimizing High School Students' Biology Learning Outcomes: Picture and Picture Method on the Topic of Living Organism Classification - Sukma Ridarwati (Journal of Mathematics Science and Computer Education, 2024)
Students' learning outcomes are the main focus of the biology learning process. However, the basic phenomenon regarding students' biology learning outcomes shows that several issues still hinder the achievement of optimal learning outcomes. Therefore, this research aims to enhance students' cognitive learning outcomes by applying the picture and picture method to living organism classification. The research used Classroom Action Research with two cycles, each consisting of 2 meetings. The first cycle covered Monera, Protista, and Fungi, while the second covered Plantae and Mammalia. The number of students involved was 36 (M=18 and F=18). Students' cognitive learning outcomes were assessed using a 10-item multiple-choice cognitive test. The data on students' cognitive learning outcomes were analyzed using percentage techniques. Students were considered to have passed if they achieved a minimum score of 70. The analysis showed a significant improvement in students' cognitive learning outcomes, from 59.8 in cycle 1 to 77.1 in cycle 2. The number of students who achieved learning mastery increased by 43.5%, from 43.5% in cycle 1 to 87% in cycle 2. Therefore, applying the picture and picture method significantly improved students' cognitive learning outcomes regarding living organism classification. The implications of this research indicate that applying the Picture and Picture method effectively enhances students' cognitive learning outcomes on the topic of living organism classification, contributing positively to biology teaching practices in the classroom.